Aronia (Chokeberry) Fruit Extract is a Potential Candidate for Managing Metabolic Syndrome in Elderly Patients - BALTACI, PELİN CİN; Eyupoglu, Ozan Emre; Kankaya, Selin; Yavuzer, Hakan (Routledge, 2025)
Objectives: Natural products like Aronia (Aronia melanocarpa) are promising candidates to manage metabolic abnormalities due to their bioactive compounds. This study aimed to evaluate the effects of daily Aronia fruit extract supplementation on the components of Metabolic Syndrome (MetS), cardiovascular health, inflammation, and atherogenic markers in elderly patients. Methods: Our study is a randomized controlled trial of 44 subjects (12 males and 32 females) diagnosed with MetS. The study groups were the intervention group (n = 22), which received daily 10 g Aronia fruit extract for 8 wk, and the control group, which did not receive the extract (n = 22). Demographics, dietary intake, and food habits were recorded by an extended survey. Baseline and post-intervention measurements of anthropometric data, dietary intake, cardiovascular parameters, blood pressure, blood lipid composition, plasma atherogenic index (PAI), triglyceride (TG), and the triglyceride-glucose index (TyG), and biomarkers of inflammation, including tumor necrosis factor-alpha (TNF-α), Interleukin 6 (IL-6), high-sensitivity C-reactive protein (hs-CRP), and oxidative stress biomarkers, were represented as delta values. Results: No significant changes were observed in anthropometric measurements within or between groups over the 8 wk. However, several cardiovascular health parameters, including diastolic blood pressure (−10.00 mmHg), PAI index (−0.06), triglycerides (−9.0 mg/dL), and low-density lipoprotein cholesterol (LDL-C) (−6.30 mg/dL) were significantly decreased in the intervention group compared to the control group at the end of 8 wk of use (p < 0.05). Inflammatory markers TNF-α (−7.87 pg/mL) and IL-6 (−0.58 pg/mL), as well as oxidative stress markers, oxidized low-density lipoprotein (ox-LDL) (−132.17 U/L) and small dense low-density lipoprotein (sdLDL) (−0.79 mg/dL), also significantly decreased in the intervention group (p < 0.001). Conclusion: Our findings suggest that daily supplementation with Aronia fruit extract significantly improves cardiovascular health markers and reduces inflammation and oxidative stress in elderly patients with MetS. Hence, Aronia extract may be an effective dietary supplement for managing MetS in high-risk groups.
Keywords: Aronia melanocarpa; IL-6; low-density lipoprotein; Metabolic syndrome; oxidized low-density lipoprotein; TNF-α